Fluorescent In Situ Hybridization Allows Rapid Identification of Microorganisms in Blood Cultures - Kempf, Volkhard A. J. (American Society for Microbiology, 2000)
Using fluorescent in situ hybridization (FISH) with rRNA-targeted fluorescently labelled oligonucleotide probes, pathogens were rapidly detected and identified in positive blood culture bottles without cultivation and biotyping. In this study, 115 blood cultures with a positive growth index as determined by a continuous-reading automated blood culture system were examined by both conventional laboratory methods and FISH. For this purpose, oligonucleotide probes that allowed identification of approximately 95% of those pathogens typically associated with bacteremia were produced. The sensitivity and specificity of these probes were 100%. From all 115 blood cultures, microorganisms were grown after 1 day and identification to the family, genus, or species level was achieved after 1 to 3 days while 111 samples (96.5%) were similarly identified by FISH within 2.5 h. Staphylococci were identified in 62 of 62 samples, streptococci and enterococci were identified in 19 of 20 samples, gram-negative rods were identified in 28 of 30 samples, and fungi were identified in two of two samples. Thus, FISH is an appropriate method for identification of pathogens grown in blood cultures from septicemic patients.